The Char and the Oystercatcher. The Value of the Wild in Rossfjord, North Norway - Olsen, Bror R (Ethnos, 2021)
This ethnographic study explores and compares the relationships that locals in Rossfjord, North Norway, have to the oystercatcher and the sea-going Arctic char respectively. Both these animals are highly valued locally, while the valuations at first look very different. The oystercatcher is protected by building bin-cases for its nesting, while the Arctic char is killed and eaten. Discussing these valuations against the value theory of David Graeber, I argue that they both connect to an underlying perception of the freedom and autonomy of wild animals, where what is not fully understood enhances an experience of wonder and appreciation of what I call the wild .